The amino-terminal signal peptide on the porcine transmissible gastroenteritis coronavirus matrix protein is not an absolute requirement for membrane translocation and glycosylation - Kapke, Paul A. (Virology, 1988)
cDNA clones mapping within the first 2601 bases of the 3′ end of the porcine transmissible gastroenteritis coronavirus (TGEV) genome were sequenced by the method of Maxam and Gilbert and an open reading frame yielding a protein having properties of the matrix (M or E1) protein was identified. It is positioned at the 5′ side of the nucleocapsid (N) gene from which it is separated by an intergenic stretch of 12 bases. The deduced M protein comprises 262 amino acids, has a molecular weight of 29,544, is moderately hydrophobic, and has a net charge of +7 at neutral pH. Thirty-four percent of its amino acid sequence is homologous with the M protein of the bovine coronavirus (BCV), 32% with that of the mouse hepatitis coronavirus (MHV), and 19% with that of the avian infectious bronchitis coronavirus (IBV). Judging from alignment with the BCV, MHV, and IBV M proteins, the amino terminus of the TGEV M protein extends 54 amino acids from the virion envelope which compares with only 28 for BCV, 26 for MHV, and 21 for IBV. Eleven of the sixteen amino-terminal amino acids are hydrophobic and the positions of charged amino acids around this sequence suggest that the first 16 amino acids comprise a potentially cleavable signal peptide for membrane insertion. A similar sequence is not found in the M proteins of BCV, MHV, or IBV. When mRNA from infected cells, or RNA prepared by in vitro transcription of the reconstructed M gene, was translated in vitro in the presence of microsomes, the M protein became translocated and glycosylated. When a protein without the amino-terminal signal peptide was made by translating a truncated version of the M gene transcript, some translocation and glycosylation also occurred suggesting that the amino-terminal signal peptide on the TGEV M protein is not an absolute requirement for membrane translocation. Interestingly, the amino-terminal peptide did not appear to be cleaved during in vitro translation in the presence of microsomes suggesting that a step in virion assembly may be required for proper exposure of the cleavage site to the signal peptidase.